MAPT mutation associated with frontotemporal dementia and parkinsonism (FTDP-17). (1st December 2016) - Haussmann, Robert; Wysocki, Marek; Brandt, Moritz D.; Hermann, Andreas; Donix, Markus
ABSTRACT: We present a 56-year-old patient suffering from frontotemporal dementia with parkinsonism linked to chromosome 17 (FTDP-17). The history included a three-generation pedigree and the patient was found to be a mutation carrier. The diagnosis was hindered by late appearance of the hypokinetic movement disorder. For clinicians, it is important to consider rare neurodegenerative disease variants in early-onset familial dementia syndromes with behavioral, cognitive, and motor symptoms.